Predictors of Long-Term Outcomes after Surgical Myocardial Revascularization - V. S. Kaveshnikov; M. A. Kuzmichkina; V. N. Serebryakova (Столичная издательская компания, 2023)
High mortality from cardiovascular diseases (CVD) requires improved approaches to the treatment of this socially significant pathology. Wide implementation of surgical myocardial revascularization makes it possible to improve significantly both life quality and expectancy in patients with coronary heart disease. The aim of this work was to analyze the literature on the impact of preoperative, operative and postoperative factors on the long-term prognosis after coronary artery bypass grafting (CABG). The review refers to both recent and earlier informative works. The target groups for this article are therapists, cardiologists, rehabilitologists, who work with patients in the short and long term after CABG. Data of Russian and foreign literature show that the long-term prognosis after CABG is largely determined by preoperative factors, in particular - age, set of cardiovascular risk factors (RF) and comorbidity, specifically - severity of coronary and systemic atherosclerosis, incident cardiovascular complications, structural and functional state of the heart. In the aggregate these factors reflect the cumulative effect and further potential of actual cardiovascular RFs, affect longterm risk of adverse events, and determine the therapeutic targets of secondary prevention. Priority of arterial conduits and completeness of revascularization are the main operative factors that determine the course of the long-term period after CABG. Among the postoperative factors, the efficiency of secondary CVD prevention is of paramount importance, in particular - achievement of target RF levels, compensation of cardiac and extracardiac pathology, adherence to the long-term medical therapy, known to improve outcomes based on specific comorbidity. Efficiency of secondary CVD prevention largely depends on patient's health attitudes, the key influence on which beyond attending physician can be provided by participation in rehabilitation programs, teaching patients the meaning and essentials of lifestyle modification and cardiovascular RFs' control.